Genetic risk factors of Alzheimer’s disease - Skrzypa, Marzena; Potocka, Natalia; Bartosik-Psujek, Halina; Zawlik, Izabela (European Journal of Clinical and Experimental Medicine, 2019)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Alzheimer’s disease (AD) is one of the most common neurodegenerative diseases, which is a serious health problem for societies that live longer. Spontaneous dominant mutations and polymorphisms of selected genes play an important role in development of AD. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. Several polymorphisms in selected genes strongly associated with development of Alzheimer’s disease were highlighted in this review: APOE, CYP46, APP, PSEN1, PSEN2, UBQLN1, BACE1, PRND, APBB2, TOMM 40. These gene polymorphisms have a significant role in the development of Alzheimer’s disease and they have potential to be biomarkers. Researchers combine efforts to find significant polymorphisms that would ensure that a person is predisposed to the occurrence of disease symptoms. This topic is often taken up by scientists seeking to develop effective genetic tests for diagnosing AD. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. Analysis of literature from web of knowledge: Web of Science (all database), NCBI and PubMed. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. We reviewed the selected important genes and polymorphisms which are most often associated with development of AD. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. It should be noted that nowadays scientists strive not to focus on only one polymorphism in the gene but on several polymorphisms in different genes concomitantly and above all on interactions between them to the diagnosis of this disease. Only this approach to AD will contribute to the creation of appropriate identification methods. Moreover, we should use the new generation tools - the platform for collecting data and personalized medicine.